VPH-7 Study of Inappropriate Antibiotic Usage in Cattle Farm in East Nusa Tenggara - Annytha Detha; Diana A Wuri; Filomena Ramos; Desi Biru; Margie Meha; Anita Lakapu (Hemera Zoa, 2018)
Antibiotics have an inhibitory effect on the growth of microorganisms [1]. The inappropriate use of antibiotics has an impact on human health, animals and the environment [2,3]. Therefore prescription Antibiotic use should be given by veterinarian. In fact, a number of breeders are practicing antibiotic beef cattle without a veterinary prescription. The purpose of this study was to determine the percentage of antibiotics used without prescription from veterinarians by farmers in Kupang City, East Nusa Tenggara.